2011
DOI: 10.1073/pnas.1104421108
|View full text |Cite
|
Sign up to set email alerts
|

Interhomolog recombination and loss of heterozygosity in wild-type and Bloom syndrome helicase (BLM)-deficient mammalian cells

Abstract: Genomic integrity often is compromised in tumor cells, as illustrated by genetic alterations leading to loss of heterozygosity (LOH). One mechanism of LOH is mitotic crossover recombination between homologous chromosomes, potentially initiated by a double-strand break (DSB). To examine LOH associated with DSBinduced interhomolog recombination, we analyzed recombination events using a reporter in mouse embryonic stem cells derived from F1 hybrid embryos. In this study, we were able to identify LOH events althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
78
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 37 publications
2
78
0
Order By: Relevance
“…S5), while those of the other six clones (I-14, -16, -17, -63, -77, and G-10) remained either intact (I-14, -16, -63, and G-10) or slightly modified (I-17 and -77) on the B6 allele (data not shown). The recovery of the I-SceI allele to the wild type can be explained by interhomolog NCO recombination in Blm-deficient ES cells, as explained in a previous paper (Larocque et al 2011), and relatively short extents of gene conversion were observed (Supplemental Fig. S5, brackets).…”
Section: Blm-deficient Es Cells With Loh But No Detectable Dels Undermentioning
confidence: 90%
See 2 more Smart Citations
“…S5), while those of the other six clones (I-14, -16, -17, -63, -77, and G-10) remained either intact (I-14, -16, -63, and G-10) or slightly modified (I-17 and -77) on the B6 allele (data not shown). The recovery of the I-SceI allele to the wild type can be explained by interhomolog NCO recombination in Blm-deficient ES cells, as explained in a previous paper (Larocque et al 2011), and relatively short extents of gene conversion were observed (Supplemental Fig. S5, brackets).…”
Section: Blm-deficient Es Cells With Loh But No Detectable Dels Undermentioning
confidence: 90%
“…The number of Dox(+)ISceIo(+) and Dox(+) ISceIo(-) colonies was significantly higher than that of Dox(-)ISceIo(+) and Dox(-)ISceIo(-) colonies, respectively, demonstrating that transient loss of BLM elevated the rate of LOH both in DSB-induced and uninduced conditions (Fig. 1F) (Larocque et al 2011). The occurrence of somatic LOH could be dependent on the cell-cycle phase.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The complex of Bloom helicase (Blm) and topoisomerase III␣ (Top3␣) 2 has been shown to convergently migrate double Holliday junctions (dHJs), an intermediate of double-strand break repair, into solely non-crossover products (1,2). The significance of this anti-recombinogenic function can be seen in the phenotype of Blm-deficient cells, which show a marked increase in sister chromatid exchanges (3) and loss of heterozygosity (4).…”
mentioning
confidence: 99%
“…Their activity is restricted to the G2/M phases of the cell cycle where they are in charge of the resolution of persistent Holliday junctions that have not been dissolved by the helicase system (Figure 1). The resolution by endonucleases implies the generation of double strand breaks and favours their repair through non-homologous end joining, an error prone pathway that may increase genome instability [70]. Interestingly, a recent report indicates that the inactivation of these endonucleases also reduces replication fork speed, highlighting their important mechanism as a back-up repair system [71].…”
Section: Rs As a Fuel Of Tumorogenesismentioning
confidence: 99%